Alzheimer's and dementia: Diagnosis, assessment, and disease monitoring global, regional, and national burden of Alzheimer's disease and other dementias (ADODs) and their risk factors, 1990–2021: A systematic analysis for the Global Burden of Disease study 2021 - Fang Wang; Dongxin Li; Xuetian Gao; Xingye Zhang; Xuanying Shi; Youquan Guo (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring, 2025)
Abstract INTRODUCTION Aging populations globally lead to growing challenges in Alzheimer's disease and other dementias (ADODs). Tracking ADODs aids health strategies. To describe global, regional, and national incidence, prevalence, death, and disability‐adjusted life years (DALYs) of ADODs in 2021, and analyze changes from 1990 to 2021. METHODS We analyzed ADODs using the 2021 Global Burden of Disease database, calculating estimated annual percentage change (EAPC), applying Joinpoint regression, and assessing risk factors. RESULTS Between 1990 and 2021, ADOD incidence, prevalence, deaths, and DALYs increased significantly. DALYs grew 295.45% and fatalities grew 167.72%. Age‐standardized rates (ASRs) rose for both genders, with women generally higher but men showing steeper increases. ASRs correlated positively with Sociodemographic Index. Risk factor contribution to DALYs and death rose by 4.1%. In 2021, metabolic factors and high fasting plasma glucose most influenced ADODs. DISCUSSION The global ADOD burden has risen since 1990. Early screening, especially for elderly women, is crucial. Policymakers must act to reverse this trend. Highlights Based on Global Burden of Disease data 1990–2021, the incidence, prevalence, mortality, and disability‐adjusted life years due to Alzheimer's and dementia are depicted globally, regionally, and nationally. The effects of gender and age were explored. The contribution of different risk factors to the disease was studied.